ANALYSIS OF CHANGES CORAL REEFS AREA USING REMOTE SENSING (A Case Study: Menjangan Island, Bali) - Hariyanto , Teguh; Lingga, Alhadir (GEOID, 2016)
Menjangan island is a small island that located in Northwest of Bali province, which is inside the area of Taman Nasional Bali Barat (TNBB) and its very potential to become a spot of marine tourism for diving and snorkeling because it has many types of flora and fauna in that island. There has been a drop in the extent of coral reefs as much as 2.02 hectare in 2007-2009. Mapping of coral reefs distribution is done by using remote sensing method and by using Landsat 8 satellite’s images. Landsat 8 Satellite imagery was used with the processing performed on the blue bands and green bands because both of those bands have the highest spectral value. Correction of the effect of water depth elimination is used for data processing. Unsupervised classification is done for object determination in satellite’s images is fully process by software. Classification result showed that there was decrease of coral reefs as 0.84 hectare in 2014-2015.